Production Potential and Income of Agricultural Holdings in Poland - Strzelecka, Agnieszka; Zawadzka, Danuta; Kurdyś-Kujawska, Agnieszka (Regional Barometer. Analyses & Prognoses, 2018)
The aim of this article is to assess the impact of production potential on the income obtained by agricultural holdings in Poland. The Farm Accountancy Data Network FADN data from 2015 was used to achieve this aim. Empirical verification of factors determining the production potential and their impact on agricultural holding income was carried out using the logistic regression model. The dependent variable was taken to be the probability that the agricultural holding would achieve annual family farm income exceeding the median value of PLN 46149,18. It was established that four variables had a statistically significant positive effect on the studied phenomenon: area of agricultural land, share of leased land in the agricultural land area, total labor expenditure and technical labor infrastructure. This means that an increase in the level of these factors increases the probability of obtaining an above median value of income by agricultural holdings.